Dosimetry of in vitro and in vivo Trials in Thermal Column Kartini Reactor for Boron Neutron Capture Therapy (BNCT) facility by using MCNPX Simulator Code - Adrian Tesalonika; Andang Widi Harto; Yohannes Sardjono; Isman Mulyadi Triatmoko (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
A dosimetry study of in vitro and in vivo trials system in thermal column of Kartini Reactor for Boron Neutron Capture Therapy (BNCT) facility has been conducted by using the Monte Carlo N-Particle Extended (MCNPX) software. Source of neutron originated from the 100 kW reactor which has been modified by the previous researcher. Models have been made by using simple geometries to represent tissues. Models of in vitro have been made by 4 spheres each has 1 cm diameter to represent tumour, whereas in vivo by 4 cylinders each has 6 cm length, 3 cm diameter, and breast soft tissue material with 1 cm sphere each located in the center of the cylinders to represent models of mouse with tumour. An increase in value of the boron concentration will increase the value of dose rate as well, then the exposure time should be shorter. The exposure times (in minutes) of in vitro trials for 20, 25, 30, 50, 75, 100, 125, and 150 μg boron/g tissues are 117.77, 117.77, 117.07, 115.69, 114.02, 112.39, 110.80, and 109.27. Whereas the exposure times of in vivo trials are 163.58, 162.78, 161.98, 158.88, 155.16, 151.61, 148.22, dan 144.98. In vitro trials have greater values of dose rate so that in vitro trials have shorter exposure time.